Effect of gluten on the digestive tract and fat body of Telodeinopus aoutii (Diplopoda). (19th December 2022) - Błaszczyk, Florentyna; Sosinka, Agnieszka; Wilczek, Grażyna; Student, Sebastian; Rost‐Roszkowska, Magdalena
Abstract: Adult specimens or larvae of invertebrates used as food for vertebrates are often maintained close to gluten so they might become vectors for cereal proteins. However, the tissues and internal organs can respond differently in animals with different feeding habits. The midgut epithelium might be a first and sufficient barrier preventing uptake and effects of gluten on the whole body, while the fat body is the main organ that accumulates different xenobiotics. Good models for such research are animals that do not feed on gluten‐rich products in their natural environment. The project's goal was to investigate alterations in the midgut epithelium and fat body of the herbivorous millipede Telodeinopus aoutii (Diplopoda) and analyze cell death processes activated by gluten. It enabled us to determine whether changes were intensified or reversed by adaptive mechanisms. Adult specimens were divided into control and experimental animals fed with mushrooms supplemented with gluten and analyzed using transmission electron microscopy, flow cytometry, and confocal microscopy. Two organs were isolated for the qualitative and quantitative analysis: the midgut and the fat body. Our study of the herbivorous T. aoutii which does not naturally feed on gluten containing diet showed that continuous and prolonged gluten feeding activates repair processes that inhibit the processes of cell death (apoptosis and necrosis) and induce an increase in cell viability. Abstract : The project's goal was to investigate alterations in the midgut epithelium and fat body of herbivorous millipedes Telodeinopus aoutii (Diplopoda) and cell death processes activated by gluten. Adult specimens were divided into control and experimental animals fed with mushrooms supplemented with gluten and analyzed using transmission electron microscopy, flow cytometry, and confocal microscopy. Two organs were isolated for the qualitative and quantitative analysis: the midgut and the fat body. The study on herbivorous invertebrates in which gluten does not persist in their natural diet showed that continuous and prolonged gluten feeding activates repair processes that inhibit the processes of cell death (apoptosis and necrosis) and induce an increase in cell viability. Thus, we can suggest that changes caused by long‐term gluten feeding will probably not affect the higher organisms.